A influência das relações sociais na sobrevivência de pequenas empresas: um estudo no setor do varejo de alimentos em Porto Alegre/RS (BRASIL) - Ramos, Cláudia Felippe (Universidade do Vale do Rio do Sinos, 2008)
The purpose of this investigation is to contribute for the studies about small companies’ competitiveness the in global market. It is taken as a theoretical assumption that social relations can explain the survivor of small food goods retails in an environment dominated by the big supermarkets chains. In Brazil, the phenomenon of survivor of these companies is hard to be understood if we just consider the concurrence between small and large companies. Theories about social relation influence on market relations are taken as an alternative view. The analysis is based on secondary and primary data. Secondary data was used as evidences to describe the food retail market in Brazil. Primary data came from three case studies of small retails located in Porto Alegre (RS/ Brasil) that were considered survivors because they had continued on activity even after the installation of big retails markets on their neighborhood. It was also considered qualitative data about the perception of two food goods the suppliers comp
Keywords: pequenas empresas; comportamento do consumidor; varejo; relações sociais; consumer behavior; retail; small companies; social relations; Ciências Sociais Aplicadas